Experiences of Iranian Nursing Students Regarding Their Clinical Learning Environment - Ebrahim Aliafsari Mamaghani; Azad Rahmani; Hadi Hassankhani; Vahid Zamanzadeh; Suzanne Campbell; Olive Fast; Alireza Irajpour (Elsevier, 2018)
Summary: Purpose: The aim of this study was to explain the experiences of Iranian nursing students regarding their clinical learning environment (CLE). Methods: Twenty-one nursing students participated in this qualitative study. Data were collected using semistructured interviews and analyzed using conventional content analysis. Results: Analysis of interviews identified six categories: educational confusion, absence of evaluation procedures, limited educational opportunities, inappropriate interactions with nursing staff, bullying culture, and discrimination. Systematic and consistent methods were not used in clinical education and evaluation of nursing students. In addition, there were inadequate interactions between nursing students and health-care staff, and most students experienced discrimination and bullying in clinical settings. Conclusion: Findings showed that the CLE of Iranian nursing students may be inadequate for high-level learning and safe and effective teaching. Addressing these challenges will require academic and practice partnerships to examine the systems affecting the CLE, and areas to be addressed are described in the six themes identified. Keywords: education, nursing, Iran, qualitative research, students, nursing